Boron-phosphorus-nitrogen synergistic smoke suppression flame retardant and preparation method thereof
By grafting groups containing phosphorus and nitrogen elements on the boron spiral ring, a boron, phosphorus, nitrogen synergistic smoke-retardant flame retardant was synthesized, which solved the problem of flammability of cotton fabrics and significantly improved the flame retardant performance and physical properties. , and achieve efficient preparation of green and environmental protection.
Patent Information
- Application Number
- CN202411678573.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-22
AI Technical Summary
Cotton fabrics are flammable, resulting in frequent fires. Existing flame retardants will release thick smoke and harmful gases at high temperatures and open flames, and their flame retardant performance is insufficient.
Using boron, phosphorus, nitrogen and synergistic smoke-retardant flame retardant, a highly efficient flame retardant is synthesized by grafting groups containing phosphorus and nitrogen on the basis of boron spiral ring, which not only improves the flame retardant performance of cotton fabrics. It also enhances its physical properties.
This flame retardant significantly improves the flame retardant and physical properties of cotton fabrics. When the weight gain rate reaches 20.4%, the LOI value of cotton fabrics reaches 44.7%, and improves tensile strength and elongation of break, and is green and pollution-free. , the product has high purity.
Smart Images

Figure CN119462768A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flame retardant preparation, and specifically relates to a boron-phosphorus-nitrogen synergistic smoke suppression flame retardant and a preparation method thereof. Background Art
[0002] Cotton fabrics made of cotton fibers have excellent moisture absorption, breathability, warmth retention, softness and biocompatibility, and are widely used in medicine, military, construction, daily life and other fields. However, cotton fabrics have the defect of being flammable and very easy to ignite. In recent years, fires caused by cotton fabrics have been increasing, posing a huge threat to people's lives and property safety. Therefore, giving cotton fabrics flame retardant properties has attracted more and more attention from researchers.
[0003] Now there are many series of flame retardants, such as halogen, phosphorus, nitrogen and boron flame retardants. Halogen flame retardants are a type of flame retardant that uses halogen atoms as the main flame retardant. It has the characteristics of low addition, good stability, affordable price and good compatibility with resin materials, and has been widely used in the early stage of flame retardant development. Although halogen flame retardants have many advantages, due to their special chemical properties, their disadvantages cannot be underestimated. They will release thick smoke and hydrogen halide gas at high temperature and open flame. Nitrogen flame retardants themselves do not have a good flame retardant effect, but they can produce non-flammable gases when burning and play a role in gas phase flame retardancy. Therefore, nitrogen flame retardants are usually used in combination with other flame retardant elements to achieve a synergistic flame retardant effect, which can significantly enhance the flame retardant properties of flame retardants. Although boron flame retardants have the effect of suppressing smoke, their flame retardancy is poor. Although phosphorus flame retardants have excellent flame retardancy, they also have disadvantages. Therefore, there is an urgent need for a synergistic flame retardant to make the flame retardant effect better. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a boron-phosphorus-nitrogen synergistic smoke suppression flame retardant and a preparation method thereof. On the basis of the boron spiro ring, groups containing phosphorus and nitrogen are grafted respectively, and the synthesized flame retardant can improve the flame retardant properties of cotton fabrics and the physical properties of cotton fabrics, and is green and pollution-free, and the product has high purity.
[0005] A boron, phosphorus and nitrogen high-efficiency synergistic flame retardant, the structural formula of the flame retardant is:
[0006]
[0007] A method for preparing a boron-phosphorus-nitrogen high-efficiency synergistic flame retardant comprises the following steps:
[0008] (1) Pentaerythritol and boric acid are mixed for reaction, and after the reaction is completed, recrystallization is performed to synthesize an intermediate product I for standby use; wherein the structural formula of the intermediate product I is:
[0009]
[0010] (2) Adding the intermediate product I and aminotrimethylene phosphoric acid aqueous solution to a reaction device, heating and stirring until dissolved and reacted, until no water vapor is distilled out; after cooling, taking out the reaction product, drying it in an oven to constant weight, and obtaining a transparent viscous liquid, which is the intermediate product II; the structural formula of the intermediate product II is:
[0011]
[0012] (3) adding urea and intermediate product II into a reaction vessel, adding a solvent, heating and stirring until dissolved;
[0013] (4) After cooling, the product obtained in step (3) is subjected to a rotary evaporator to remove excess solvent, and finally dried to a constant weight to obtain a light yellow oily liquid, which is the final product, i.e., the target flame retardant.
[0014] Preferably, in step (1), the molar ratio of pentaerythritol to boric acid is 1:2-7.
[0015] Preferably, in step (1), the reagent used for recrystallization is any one of acetone or acetonitrile.
[0016] Preferably, in step (2), the molar ratio of the intermediate product I to the aminotrimethylene phosphoric acid aqueous solution is 1:2-5.
[0017] Preferably, in step (2), the reaction heating temperature is 110-130°C; and then cooled to 40-60°C.
[0018] Preferably, in step (3), the molar ratio of the intermediate product II to urea is 1:2-5.
[0019] Preferably, in step (3), the solvent used is toluene, ethylbenzene or any one of them or a mixture thereof in any proportion.
[0020] Preferably, in step (3), the heating temperature is 150-160° C. and the reaction time is 1-5 h.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention provides a boron-phosphorus-nitrogen synergistic flame retardant, wherein the flame retardant molecule contains a variety of flame retardant elements, which can play a synergistic flame retardant role and obtain higher flame retardant performance. On the one hand, the flame retardant can be connected to the cotton fabric through chemical bonds, so that the flame retardant cotton fabric obtains a certain water washing resistance. On the other hand, the flame retardant effect is improved. When the weight gain rate reaches 20.4%, the LOI value of the treated fabric reaches 44.7%, and the mechanical properties of the fabric are also enhanced. The tensile strength of the cotton fabric treated with the flame retardant exceeds that of the pure cotton fabric, and the elongation at break is also improved, with the highest elongation at break increasing by about 12.9%.
[0023] The preparation method provided by the invention has the advantages of simple synthesis process, no toxic gas release, high product purity, and no harm to the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The flame retardant synthesis route of the present invention is shown in FIG.
[0025] Figure 2 The present invention provides a scanning electron microscope photograph comparing the carbon residue after burning a boron-phosphorus-nitrogen synergistic flame retardant on pure cotton fabric, treated cotton fabric and treated cotton.
[0026] Figure 3 It is the limiting oxygen index value of the cotton fabric after being finished with the synthetic flame retardant in Example 1 of the present invention.
[0027] Figure 4 This is a diagram showing the physical properties of cotton fabric and pure cotton fabric after being finished with a synthetic flame retardant according to the present invention. DETAILED DESCRIPTION
[0028] The accompanying drawings are only for illustrative purposes; it should be understood that common knowledge or prior art in the embodiments may be omitted; the cases mentioned below are only used to explain the present invention in order to facilitate the description of the present invention and simplify the description, and therefore, cannot be understood as limiting the present invention.
[0029] The present invention is described in detail below with reference to the embodiments.
[0030] Example 1
[0031] like Figure 1As shown, first, 6.801g (0.11mol) of boric acid and 9.6g (0.05mol) of pentaerythritol were mixed with 50mL of toluene (Toluece) in a 250mL single-necked flask. A glass water separator connected to a spherical condenser was connected to the top of the flask, and an oil bath device with a thermometer and a magnetic stirrer were installed below the flask. After opening the condensed water, the system was reacted in a 110°C oil bath until no water was produced in the water separator. Then continue heating until the toluene in the flask is completely evaporated. After the reaction, the material in the flask was recrystallized with acetone and then dried at 50°C to constant weight, and finally 9.748g of white solid was obtained, which was the intermediate product I.
[0032] 9.4 g (0.05 mol) of the intermediate product I ground into powder and 59.8 g (0.1 mol) of aminotrimethylene phosphoric acid aqueous solution were added to a three-necked flask, mixed evenly, and placed in the same apparatus as in step (1). After stirring, the reaction was carried out in an oil bath at 130°C until no water vapor was distilled out. After the temperature was lowered, the mixture was dried in an oven at 50°C to constant weight to obtain a transparent viscous liquid, which was the intermediate product II.
[0033] 37.5g (0.05mol) of intermediate product II and 12.12g (0.2mol) of urea were added to a three-necked flask, and then 100mL of water was added as a solvent. The three-necked flask was equipped with a spherical condenser, a magnetic stirrer, and an oil bath device with a thermometer. After turning on the condensed water and stirring, the system was heated and refluxed in a 160°C oil bath for about 2 hours until the solution changed from a white emulsion to a colorless and transparent state. After the solution was cooled, the solution was transferred to a pear-shaped bottle, and the excess solvent was removed by a rotary evaporator. Finally, it was dried at 50°C to constant weight, and finally a light yellow oily liquid was obtained, which was the final product.
[0034] Example 2
[0035] First, 6.801g (0.11mol) of boric acid and 9.6g (0.05mol) of pentaerythritol were mixed with 60mL of ethylbenzene in a 250mL single-necked flask. A glass water separator connected to a spherical condenser was connected to the top of the flask, and an oil bath device with a thermometer and a magnetic stirrer were installed below the flask. After opening the condensed water, the system was reacted in a 120°C oil bath until no water was produced in the water separator. Then continue heating until the toluene in the flask is completely evaporated. After the reaction, the material in the flask was recrystallized with acetone and then dried at 50°C to constant weight, and finally 9.748g of white solid was obtained, which was the intermediate product I.
[0036] 18.8 g (0.1 mol) of the intermediate product I ground into powder and 119.6 g (0.2 mol) of aminotrimethylene phosphoric acid were added to a three-necked flask, mixed evenly, and placed in the same apparatus as in step (1). After stirring, the reaction was carried out in an oil bath at 140°C until no water vapor was distilled out. After the temperature was lowered, the mixture was dried in an oven at 50°C to constant weight to obtain a transparent viscous liquid, which was the intermediate product II.
[0037] 75.0g (0.1mol) of intermediate product II and 24.024g (0.4mol) of urea were added to a three-necked flask, and then 200mL of water was added as a solvent. The three-necked flask was equipped with a spherical condenser, a magnetic stirrer, and an oil bath device with a thermometer. After turning on the condensed water and stirring, the system was heated under reflux at 170°C oil bath for about 2 hours until the solution changed from a white emulsion to a colorless and transparent state. After the solution was cooled, the solution was transferred to a pear-shaped bottle, and the excess solvent was removed by a rotary evaporator. Finally, it was dried at 50°C to constant weight, and finally a light yellow oily liquid was obtained, which was the final product.
[0038] Example 3
[0039] The synthesis method of the intermediate product I is the same as that of Example 1.
[0040] 18.8 g (0.1 mol) of the intermediate product I ground into powder and 179.4 g (0.3 mol) of aminotrimethylene phosphoric acid were added to a three-necked flask, mixed evenly, and placed in the same apparatus as in step (1). After stirring, the reaction was carried out in an oil bath at 140°C until no water vapor was distilled out. After the temperature was lowered, the mixture was dried in an oven at 50°C to constant weight to obtain a transparent viscous liquid, which was the intermediate product II.
[0041] 75.0g (0.1mol) of intermediate product II and 30.03g (0.5mol) of urea were added to a three-necked flask, and then 150mL of water was added as a solvent. The three-necked flask was equipped with a spherical condenser, a magnetic stirrer, and an oil bath device with a thermometer. After turning on the condensed water and stirring, the system was heated under reflux at 160°C oil bath for about 3 hours until the solution changed from a white emulsion to a colorless and transparent state. After the solution was cooled, the solution was transferred to a pear-shaped bottle, and the excess solvent was removed by a rotary evaporator. Finally, it was dried at 50°C to constant weight, and finally a light yellow oily liquid was obtained, which was the final product.
[0042] Example 4
[0043] The synthesis method of the intermediate product I is the same as that of Example 1.
[0044] 18.8 g (0.1 mol) of the intermediate product I ground into powder and 239.2 g (0.4 mol) of aminotrimethylene phosphoric acid were added to a three-necked flask, mixed evenly, and placed in the same apparatus as in step (1). After stirring, the reaction was carried out in an oil bath at 120°C until no water vapor was distilled out. After the temperature was lowered, the mixture was dried in an oven at 50°C to constant weight to obtain a transparent viscous liquid, which was the intermediate product II.
[0045] 75.0g (0.1mol) of intermediate product II and 36.04g (0.6mol) of urea were added to a three-necked flask, and then 170mL of water was added as a solvent. The three-necked flask was equipped with a spherical condenser, a magnetic stirrer, and an oil bath device with a thermometer. After turning on the condensed water and stirring, the system was heated under reflux at 170°C oil bath for about 2 hours until the solution changed from a white emulsion to a colorless and transparent state. After the solution was cooled, the solution was transferred to a pear-shaped bottle, and the excess solvent was removed by a rotary evaporator. Finally, it was dried at 50°C to constant weight, and finally a light yellow oily liquid was obtained, which was the final product.
[0046] Example 5
[0047] The synthesis method of the intermediate product I is the same as that of Example 1.
[0048] 1.88 g (0.01 mol) of the intermediate product I ground into powder and 11.96 g (0.02 mol) of aminotrimethylene phosphoric acid were added to a three-necked flask, mixed evenly, and placed in the same apparatus as in step (1). After stirring, the reaction was carried out in an oil bath at 120°C until no water vapor was distilled out. After the temperature was lowered, the mixture was dried in an oven at 50°C to constant weight to obtain a transparent viscous liquid, which was the intermediate product II.
[0049] 15g (0.02mol) of intermediate product II and 4.805g (0.08mol) of urea were added to a three-necked flask, and then 150mL of water was added as a solvent. The three-necked flask was equipped with a spherical condenser, a magnetic stirrer, and an oil bath device with a thermometer. After turning on the condensed water and stirring, the system was heated under reflux at 170°C oil bath for about 2 hours until the solution changed from a white emulsion to a colorless and transparent state. After the solution was cooled, the solution was transferred to a pear-shaped bottle, and the excess solvent was removed by a rotary evaporator. Finally, it was dried at 50°C to constant weight, and finally a light yellow oily liquid was obtained, which was the final product.
[0050] like Figure 2 The following are scanning electron microscope photos of the carbon residues after the flame retardant of the present invention is burned on pure cotton fabric, treated cotton fabric and treated cotton. Figure 2It can be seen that a layer of particulate matter is enriched on the surface of the fabric fibers after the flame retardant treatment, which indicates that the flame retardant has been successfully attached to the cotton fabric. After burning, it can be observed that the cotton fibers remain intact, but some small bubbles are added to their surface. This is caused by the release of ammonia gas by the nitrogen elements in the ammonium groups that did not participate in the grafting reaction after heating. After further magnification, it can be observed that there are film-like substances and block-like particles on the surface of the cotton fibers. The results show that the use of the flame retardant significantly improves the carbonization performance of the fabric.
[0051] like Figure 3 As shown, it is the limiting oxygen index test result of the cotton fabric after finishing with the synthetic flame retardant in Example 1. The pure cotton fabric is very easy to burn in the atmospheric environment, and the LOI value is only 18.3%. When the weight gain of the cotton fabric after finishing reaches 10.1%, the LOI value increases to 33.2%, and it can achieve self-extinguishing under natural conditions, which has reached the standard of flame-retardant cotton fabric. Continuing to increase the concentration of the flame retardant, the LOI value of the fabric continues to increase. When the weight gain rate reaches 20.4%, the LOI value of the treated fabric reaches 44.7%. The flame retardant involved in the present invention has a good flame retardant effect on cotton fabrics, and the addition amount is small, and the flame retardant efficiency is high.
[0052] like Figure 4 As shown, the tensile strength test diagram of cotton fabric and pure cotton fabric treated with synthetic flame retardant in Example 1. The warp and weft tensile strengths of pure cotton fabric are 474 and 437N respectively, and the elongation at break is 5.23 and 29.36% respectively. The tensile strength of cotton fabric treated with flame retardant exceeds that of pure cotton fabric, and the elongation at break is also improved, with the highest elongation at break increasing by about 12.9%. This may be because when the content of flame retardant is low, all P-ONH4+ in the flame retardant reacts with -CH2OH on cellulose, resulting in excessive cross-linking. When the content of flame retardant increases, excessive flame retardant competes with -CH2OH on cellulose, resulting in part of the gap being filled by flame retardant, and after being subjected to tension, part of it is borne by the flame retardant molecules, thereby improving the tensile strength and increasing a certain toughness.
[0053] Those skilled in the art will appreciate that the experimental examples shown here are intended to help readers understand the principles of the present invention, and it should be understood that the protection scope of the present invention is not limited to such specific statements and embodiments. Those skilled in the art can make various other variations that do not deviate from the essence of the present invention based on the technical revelations disclosed in the present invention, and these variations are still within the protection scope of the present invention.
Claims
1. A boron, phosphorus and nitrogen high-efficiency synergistic flame retardant, the structural formula of the flame retardant is:
2. A method for preparing a boron, phosphorus and nitrogen high-efficiency synergistic flame retardant, characterized in that: The steps include: (1) taking pentaerythritol and boric acid to react, and after the reaction is completed, performing recrystallization to synthesize an intermediate product I for later use; (2) adding the intermediate product I and aminotrimethylene phosphoric acid aqueous solution to a reaction device, heating and stirring until they are dissolved and reacted until no water vapor is distilled out; after cooling, taking out the reaction product, drying it in an oven to constant weight, and obtaining a transparent viscous liquid, which is the intermediate product II; (3) adding urea and intermediate product II into a reaction vessel, adding a solvent, heating and stirring until dissolved; (4) After cooling, the product obtained in step (3) is subjected to a rotary evaporator to remove excess solvent, and finally dried to a constant weight to obtain a light yellow oily liquid, i.e., the target flame retardant.
3. The method for preparing a boron, phosphorus and nitrogen high-efficiency synergistic flame retardant according to claim 2, characterized in that: In the step (1), the molar ratio of pentaerythritol to boric acid is 1:2-7.
4. The method for preparing a boron, phosphorus and nitrogen high-efficiency synergistic flame retardant according to claim 2, characterized in that: In the step (1), the reagent used for recrystallization is any one of acetone and acetonitrile.
5. The method for preparing a boron, phosphorus and nitrogen high-efficiency synergistic flame retardant according to claim 2, characterized in that: In the step (2), the molar ratio of the intermediate product I to the aminotrimethylene phosphoric acid aqueous solution is 1:2-5.
6. The method for preparing a boron, phosphorus and nitrogen high-efficiency synergistic flame retardant according to claim 2, characterized in that: In the step (2), the reaction heating temperature is 110-130°C and then cooled to 40-60°C.
7. The method for preparing a boron, phosphorus and nitrogen high-efficiency synergistic flame retardant according to claim 2, characterized in that: In the step (3), the molar ratio of the intermediate product II to urea is 1:2-5.
8. The method for preparing a boron, phosphorus and nitrogen high-efficiency synergistic flame retardant according to claim 2, characterized in that: In the step (3), the solvent used is any one of toluene and ethylbenzene or a mixture thereof in any proportion.
9. The method for preparing a boron, phosphorus and nitrogen high-efficiency synergistic flame retardant according to claim 2, characterized in that: In the step (3), the heating temperature is 150-160° C. and the reaction time is 1-5 hours.
Citation Information
Patent Citations
Boron-nitrogen-phosphorus-integrated polymeric type flame retardant and preparing method thereof
CN105440291A
Chelating coordination type phosphorus-boron-nitrogen synergistic flame retardant and preparation method thereof
CN112442895A
Reactive phosphorus-nitrogen-boron synergistic flame retardant and preparation method thereof
CN114671916A
Phosphorus-nitrogen-boron durable flame retardant and preparation method thereof
CN117430638A